OWE-035 Ambulatory liver services avoid admissions and reduce length of stay with high patient satisfaction. (8th June 2018) - Jennings, J; Dillon, J; Chimakurthi, C; Gibson, S; Crosswaite, A; Harding, S; Roberts, C; Hiles, T; McSorley, P; Murdoch, S; Jones, RL
Abstract : Introduction: Inpatient bed pressures in the NHS mean that ambulatory service development is needed. Day case and short stay units developed for elective surgery in our trust were not suited to the needs of patients with liver disease. Services managed through semi-acute pathways Resulted in unpredictable waiting times, unplanned admissions and poor patient experience. Following a pilot project in 2016–17, we describe the 2nd phase in implementing ambulatory care services utilising a re-commissioned 4 bed ward bay in a large liver centre. Primary aims were admission avoidance (AA) and inpatient bed day savings. Secondary aims were to achieve >70% occupancy, deliver excellent patient experience, provide facilities for earlier discharge (ED). Methods: We identified initial criteria for service delivery through a specialist nurse led unit. Patient episodes were coded to identify procedures, infusion treatments and AA/ED attendances. Safety was assessed by procedure complication rates and patient readmission rates. We used Survey Monkey ® to assess patient experience. Bed savings were identified from historical length of stay data in 2015–16. Results: Between 1 st May–31 st Dec 2017 there were 705 attendances. Of these: 371 large volume paracentesis, 49 urgent liver biopsy, 80 infusions, 46 ascites follow-up and 159 AA/ED indications. Based on a 2.5 day admission for paracentesis, 927 inpatient bed days were saved for this indication and at least 420 urgent, semi-acute or unplanned admissions were avoided. Utilisation increased from 68 attendances/month to 115 in Dec 2017. The unit reached 70% occupancy at 3 months. By Dec 2017 occupancy was >90%. There were 3 readmissions and 1procedure complication. 95% of patients thought that explanations regarding procedure were very clear and 95% that they were well informed throughout the day. 95% would recommend the service to friends and family. Conclusion: A clear benefit to patients and the service was seen during the first 6 months of opening this unit. We continue to identify indications for use. Other benefits include a growing list of clear admission avoidance/early discharge for other indications. Bed day release has helped patient flow for admissions. Costs incurred in developing a specialist nursing team are offset by their other roles and transfer of ward nursing costs. Unpredicted benefits include a contribution to an overall improvement in ward quality metrics, and release of junior doctor time to direct inpatient management.